2018
DOI: 10.3389/fphys.2018.01402
|View full text |Cite
|
Sign up to set email alerts
|

Human Atrial Arrhythmogenesis and Sinus Bradycardia in KCNQ1-Linked Short QT Syndrome: Insights From Computational Modelling

Abstract: Atrial fibrillation (AF) and sinus bradycardia have been reported in patients with short QT syndrome variant 2 (SQT2), which is underlain by gain-of-function mutations in KCNQ1 encoding the α subunit of channels carrying slow delayed rectifier potassium current, IKs. However, the mechanism(s) underlying the increased atrial arrhythmogenesis and impaired cardiac pacemaking activity arising from increased IKs remain unclear. Possible pharmacological interventions of AF in the SQT2 condition also remain to be elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…In a recent simulation study of atrial arrhythmia substrates in SQT2, simulated quinidine application increased atrial ERP for both V307L and V141M KCNQ1 mutations. However, it was not effective at restoring APD in the V141M setting [78] though it decreased the dominant frequency of excitation for both mutations, consistent with a potential role for rate if not rhythm control. The in silico observations regarding lack of effectiveness of quinidine for rhythm control with V141M correspond well to clinical findings in which recurrent AF associated with the V141M KCNQ1 mutation failed to respond to antiarrhythmic agents including quinidine [77].…”
Section: Insights From Preclinical Sqts Studies Into Arrhythmia Substmentioning
confidence: 83%
See 3 more Smart Citations
“…In a recent simulation study of atrial arrhythmia substrates in SQT2, simulated quinidine application increased atrial ERP for both V307L and V141M KCNQ1 mutations. However, it was not effective at restoring APD in the V141M setting [78] though it decreased the dominant frequency of excitation for both mutations, consistent with a potential role for rate if not rhythm control. The in silico observations regarding lack of effectiveness of quinidine for rhythm control with V141M correspond well to clinical findings in which recurrent AF associated with the V141M KCNQ1 mutation failed to respond to antiarrhythmic agents including quinidine [77].…”
Section: Insights From Preclinical Sqts Studies Into Arrhythmia Substmentioning
confidence: 83%
“…This mutation results in an instantaneous component of I Ks current and initial modelling (using a human ventricular model and rabbit sinoatrial node model) showed abbreviation of ventricular APs and abolition of pacemaking [49]. Our recent human atrial and sinus node simulations have shown that the distinct changes to I Ks produced by the two mutations can account for their different phenotypes in respect of sinus bradycardia [78]. Only the V141M mutation exerted a marked effect on simulated sinoatrial node pacemaking rate, due to its greater effect in increasing I Ks over the diastolic membrane potential range (the increased I Ks resulting in a slowed diastolic depolarisation) [78].…”
Section: Synergy Between Clinical and Preclinical Studies In Understamentioning
confidence: 87%
See 2 more Smart Citations
“…Equation (1) was solved using a finite difference PDE solver based on the explicit forward Euler method and Strang splitting scheme. Effects of the N588K-hERG mutation and its modulation by propafenone on effective refractory period (ERP), conduction velocity (CV), excitation wavelength (WL; given by WL = CV × ERP), and spiral wave dynamics were determined using 1D and 2D atrial tissue models with spatial step, Δx = 0.25 mm, as described previously [17], [18]. Re-entry in the 2D sheet was initiated using an S1-S2 cross-shock protocol.…”
Section: Tissue Simulationsmentioning
confidence: 99%